Increased Serum ox-LDL Levels Correlated with Lung Function, Inflammation, and Oxidative Stress in COPD - Yongchun Shen; Ting Yang; Shujin Guo; Xiao'ou Li; Lei Chen; Tao Wang; Fuqiang Wen (Hindawi Limited, 2013)
Chronic obstructive pulmonary disease (COPD) is associated with abnormal inflammation and high oxidative stress. Studies suggest that oxidized low density lipoprotein (ox-LDL) is involved in diseases associated with oxidative stress and inflammation. However, no data on the possible relationship between COPD and ox-LDL are available. This study compared serum levels of ox-LDL in 48 COPD patients and 32 health controls and correlated them with lung function, systematic inflammation, and oxidative stress. Serum levels of ox-LDL, C-reactive protein (CRP), and oxidative stress (measured by reactive oxygen species, ROS) were analyzed using commercial kits. Mean levels of serum ox-LDL were significantly higher in COPD patients than in controls (18.62±7.56 versus 12.57±5.90 mU/L, P<0.05). Serum levels of CRP and ROS were also significantly higher in COPD patients. Serum levels of ox-LDL in COPD patients correlated inversely with FEV1% predicted, an index of lung function (r=−0.347, P=0.016), while they correlated positively with CRP and ROS levels. These results suggest that serum levels of ox-LDL are increased in COPD patients and that these levels are associated with lung function, inflammation, and oxidative stress in COPD. Future studies are needed to determine whether and how ox-LDL plays a role in COPD.